Correlation Between The Indonesian Versions of Montreal Cognitive Assessment (MoCA-INA) and Visual Cognitive Assessment Test (VCAT-INA) as Cognitive Screening Tools - Fitri, Fasihah Irfani; Rambe, Aldy S; Ong, Paulus Anam; Gultom, Ika Mariana (International Journal of Human and Health Sciences (IJHHS), 2022)
Background and purpose: Screening for cognitive impairment has become increasingly important as the population ages, especially using tools that is not mainly affected my translational process so it can be used in multilingual population. The aim of this study was to determine the correlation between the Indonesian version of Montreal Cognitive Assessment (MoCA-INA) and Visual Cognitive Assessment Test (VCAT-INA) as cognitive screening tools. Methods: This was a cross sectional study involving subjects recruited for cognitive screening in general population and memory clinic Adam Malik General Hospital Medan Indonesia between December 2019 and April 2020. All subjects underwent physical and neurologic examination and cognitive assessment including MoCA-INA and VCAT-INA, that was adapted from the original version. Results: A total of 104 subjects were studied, consisted of 41 (39.4%) males and 63 (60.4%) females. The mean age of subjects was 64.4±10.07 years and ranged from 41-82 years. Most of the subjects had 12 years of education (45 subjects; 43.3%). Most of the subjects had abnormal MoCA-INA and VCAT-INA scores. Both scores showed comparable result but VCATINA showed lower average and a broader range of scores. There was a strong positive significant correlation between the scores (r=0.815; p < 0.001). Conclusions: MoCAINA score is strongly correlated with VCAT-INA score. As visual-based test, VCAT-INA can be applied as a cognitive screening tool in daily clinical practice without significant language barrier. International Journal of Human and Health Sciences Vol. 06 No. 01 January’22 Page: 47-54